Regulations Regarding the Practice of Psychotherapy in Quebec: One Step Forward, Two Steps Backwards? - Drapeau, Martin (Canadian Journal of Counselling and Psychotherapy, 2016)
Quebec innovated by recently passing a new law, commonly known as “Bill 21,” that regulates several clinical activities considered at risk activities, including psychotherapy. Bill 21 is meant to support “competent access,” recognizing different groups of professionals, including counsellors, who may offer psychotherapy services, with conditions. For practitioners who are neither psychologists nor physicians, these conditions include the obligation to be a member of a professional regulatory body, possession of a master’s degree, and successful completion of a 600-hour clinical internship and 765 hours of theoretical training. The responsibility for assessment of eligibility for a psychotherapy permit of all psychotherapists who are not psychologists or physicians and the authority to issue psychotherapy permits lie with the Order (College) of Psychologists of Quebec (OPQ). However, the OPQ appears to interpret the law in a way that imposes additional requirements on psychotherapists.